Reducing the dimensions of acoustic devices using anti-acoustic-null media. (23rd January 2018) - Li, Borui; Sun, Fei; He, Sailing
Abstract: An anti-acoustic-null medium (anti-ANM), a special homogeneous medium with anisotropic mass density, is designed by transformation acoustics (TA). Anti-ANM can greatly compress acoustic space along the direction of its main axis, where the size compression ratio is extremely large. This special feature can be utilized to reduce the geometric dimensions of classic acoustic devices. For example, the height of a parabolic acoustic reflector can be greatly reduced. We also design a brass–air structure on the basis of the effective medium theory to materialize the anti-ANM in a broadband frequency range. Numerical simulations verify the performance of the proposed anti-ANM.